Environmental specialization and cryptic genetic divergence in two massive coral species from the Florida Keys Reef Tract. Issue 14 (10th June 2021) - Rippe, John P.; Dixon, Groves; Fuller, Zachary L.; Liao, Yi; Matz, Mikhail
Abstract: Broadcast‐spawning coral species have wide geographical ranges spanning strong environmental gradients, but it is unclear how much spatially varying selection these gradients actually impose. Strong divergent selection might present a considerable barrier for demographic exchange between disparate reef habitats. We investigated whether the cross‐shelf gradient is associated with spatially varying selection in two common coral species, Montastraea cavernosa and Siderastrea siderea, in the Florida Keys. To this end, we generated a de novo genome assembly for M. cavernosa and used 2bRAD to genotype 20 juveniles and 20 adults of both species from each of the three reef zones to identify signatures of selection occurring within a single generation. Unexpectedly, each species was found to be composed of four genetically distinct lineages, with gene flow between them still ongoing but highly reduced in 13.0%–54.7% of the genome. Each species includes two sympatric lineages that are only found in the deep (20 m) habitat, while the other lineages are found almost exclusively on the shallower reefs (3–10 m). The two "shallow" lineages of M. cavernosa are also specialized for either nearshore or offshore: comparison between adult and juvenile cohorts indicates that cross‐shelf migrants are more than twice as likely to die before reaching adulthood than local recruits. S. siderea and M. cavernosa are among the most ecologically successful species on the Florida Keys Reef Tract, and this work offers important insight into the genomic background of divergent selection and environmental specialization that may in part explain their resilience and broad environmental range.